McCullough and Berglund on mastering Git. - Berglund, Tim; McCullough, Matthew (Matthew J.) (O'Reilly Media, 2011)
"Learn the Git version control system through visual examples and step-by-step explanations. In this in-depth video course, experts Matthew McCullough and Tim Berglund help you explore the full spectrum of Git, from the foundations of how objects are hashed to the practical commands you need to be productive every day. You'll learn how Git not only incorporates the best features of existing source control systems, but also includes unique distributed capabilities that make version control commands available without connectivity"--Resource description page.